-1+8y/5=-5/3-y+3y/5

Simple and best practice solution for -1+8y/5=-5/3-y+3y/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1+8y/5=-5/3-y+3y/5 equation:


y in (-oo:+oo)

(8*y)/5-1 = (3*y)/5-y-5/3 // - (3*y)/5-y-5/3

(8*y)/5+y-((3*y)/5)-(-5/3)-1 = 0

(8*y)/5+y+(-3/5)*y+5/3-1 = 0

2*y+2/3 = 0 // - 2/3

2*y = -2/3 // : 2

y = -2/3/2

y = -1/3

y = -1/3

See similar equations:

| 9.5x+3=5.5x+4 | | (4/5)+(2/7)= | | 30z+(27z-5)=-28 | | 17/9= | | 17x-(5x-9)=21 | | -1+y/3=0 | | 3(x)-8=100 | | 6y+3x=15 | | 11y-12/8+3y/5=6y-1/8 | | (2x)^0/-2^4 | | 11+25y+29y=-14+27y-18y | | -5y/4+8/3=0 | | x+8y=38 | | (3r^2+10r-8)(12r^2-4r+3)= | | -9/4+3y+4=-9y-3 | | 2(2x-3)=3(x+6) | | 4(5x+3)=-5(x-2) | | 9k^2+5k+4=0 | | x^2+16x+105=0 | | x+4y=18 | | 62=9x+8 | | 12(5+6m)+16=-90 | | -40y+8x+48=0 | | 4z/5-7/3=2z/3-2z/3 | | -40x+8y+48=0 | | (x+6)(x+6)(x-8)(4x-5)=0 | | 1.2x+4(0.4x+8)=24 | | x^2-4x+4=o | | -(11y+8)-20y-25y=21 | | 1.2x+4(0.4+8)=24 | | -3y-12/9+y=-7y-10/3 | | 9+49= |

Equations solver categories